OPTIMASI METODE AHP DALAM MENENTUKAN MEDIA PROMOSI BAGI MAHASISWA BARU PADA STIKOM TUNAS BANGSA PEMATANGSIANTAR - Sundari, Riski; Safii, Muhammad; Hartama, Dedy; Poningsih, Poningsih (STMIK Budi Darma, 2017)
Promotion is a very important issue for every academic because it involves the continuation of the academic development. STIKOM Tunas Bangsa is one of PTS in North Sumatera which is engaged in computer science. The process of admission of new students has the same procedure that is doing promotion to various regions in order to obtain human resources who will be a student of the college. To conduct promotional activities, STIKOM Tunas Bangsa through the marketing team must consider many factors, including promotional media used to obtain new students. From the above problems the author wants to create a decision support system that can provide solutions to the problem. One of the methods DSS that can be used is the method of Analytical Hierarchy Process (AHP). AHP is a decision support model developed by Thomas L. Saaty. This decision support model will describe the problem of multy factor or complex multi criteria into a hierarchy, according to the time (1993) the hierarchy is defined as a representation of a complex problem in a multi-level structure where the first level is the goal, and followed by the factor level , Criteria, sub criteria, and so on down to the last level of the alternative. With a hierarchy, a complex problem can be broken down into groups that are then organized into a hierarchical form so that the problem will seem more structured and systematic. From the results of this study is expected to assist the management, especially the marketing team in providing the best media promotion solutions for new students at STIKOM Tunas Bangsa Pematangsiantar.